A Study of Stoicism in EFL Students’ Learning Process - Serlinia Rambu; Wilem Andro Benu; Yoti Julisa Nabuasa; Selvina Anin (Pusat Kegiatan Belajar Masyarakat (PKBM) Sambi Poleng, 2023)
This study aimed to find out students’ emotional problems in the learning process and how the theory of stoicism can be applied to overcome those problems. This study used a descriptive qualitative research design that focuses on data presentation. The semi-structured interview was used to get deep information about this topic. There are four university students who were taken as the participants of this study. The result showed that there are several emotional problems in the learning process such as anxiety, lack of motivation, academic stress, etc. In Fact, those problems can be overcome by applying stoicism consciously or unconsciously.